2002
DOI: 10.1152/japplphysiol.00209.2002
|View full text |Cite
|
Sign up to set email alerts
|

Deep breaths, methacholine, and airway narrowing in healthy and mild asthmatic subjects

Abstract: Crimi, Emanuele, Riccardo Pellegrino, Manlio Milanese, and Vito Brusasco. Deep breaths, methacholine, and airway narrowing in healthy and mild asthmatic subjects. J Appl Physiol 93: 1384-1390, 2002. First published June 21, 2002 10.1152/japplphysiol.00209.2002Deep breaths taken before inhalation of methacholine attenuate the decrease in forced expiratory volume in 1 s and forced vital capacity in healthy but not in asthmatic subjects. We investigated whether this difference also exists by using measurements no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 20 publications
5
70
3
1
Order By: Relevance
“…Radial strain increased ASM length, whereas under the experimental conditions applied, axial distension reduced ASM length. These in vitro findings are, however, in agreement with those reported in vivo by CRIMI et al [70], showing that in both asthmatic and healthy humans, multiple deep inspirations taken prior to inhaling a constrictor agent led to airway narrowing rather than dilatation, thus arguing against the existence of an in vivo bronchoprotective mechanism.…”
Section: Other Modulators Of Asmsupporting
confidence: 91%
See 1 more Smart Citation
“…Radial strain increased ASM length, whereas under the experimental conditions applied, axial distension reduced ASM length. These in vitro findings are, however, in agreement with those reported in vivo by CRIMI et al [70], showing that in both asthmatic and healthy humans, multiple deep inspirations taken prior to inhaling a constrictor agent led to airway narrowing rather than dilatation, thus arguing against the existence of an in vivo bronchoprotective mechanism.…”
Section: Other Modulators Of Asmsupporting
confidence: 91%
“…It was postulated by KING et al [26] that this post-oscillation refractoriness of resting ASM was responsible for the bronchoprotective effect of deep inspiration taken before bronchoprovocation seen in nonasthmatics, and that in asthmatics, this refractoriness might be absent. CRIMI et al [70], however, found that this effect was only evident when lung function parameters preceded by a full inflation were used, such as FEV1 or forced vital capacity. Using parameters not preceded by full inflation, (e.g.…”
Section: Evidence Of Asm Involvement In Asthmamentioning
confidence: 98%
“…Most notably, expiratory flow derived from maximal expiration (i.e. FEV1) is differentially altered compared with flow during expiration from a submaximal expiration (partial expiration) [7,15]. The FEV1 necessitates a DI, which is significant in that potential bronchoprotective effects become intertwined with the bronchodilatory effects of DI.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, when manoeuvres other than maximal expiration are used to assess the effects of DI prior to challenge; for example, in expiration from a submaximal lung volume (i.e. partial exhalation), bronchoprotection is not observed [7,15].…”
mentioning
confidence: 99%
“…This protective effect is reduced in asthmatics and also in obese individuals in comparison to lean controls. 49,50 Therefore, the net result in the airways of the obese subjects would be more substantial airway smooth muscle contraction and airway narrowing.…”
Section: Mechanical Airway Changes In Obesitymentioning
confidence: 99%